Differences in the competitive performance indicators of Grand Slam winners at the Australian Open and Wimbledon in 2021 - Jozic, J.; Lukenda, Ž.; Milanovic, M.; Perinovic, V.; Špehar, N. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The aim of this research study was to analyze the differences in the competitive performances of the winner of the Australian Open and Wimbledon Grand Slam tournaments in 2021. The data is based on his performance in the seven matches played in each of the Grand Slam tournaments. In a total of 14 matches, the data collected on his competitive performances is divided into 13 variables representing basic statistical indicators of competitive performances in tennis. Statistically significant differences were obtained through the analysis of the performance variables between the two tournaments, with the most prominent differences observed in service performance. In particular, variables related to the performance of the first and second serves, as well as the "percentage of points won on the first serve," exhibited statistically significant differences between the Australian Open and Wimbledon tournaments. These statistically significant differences are attributed to the difference in playing surfaces, with the Australian Open being held on a hard surface and Wimbledon on a grass surface. The ball bounces differently on these surfaces, affecting the angle and speed of the ball, which in turn impacts the player's service performance.